RELIGIOUS PERSPECTIVES IN BUSINESS ETHICS - Anwar, M. Ansor (Entrepreneur, 2011)
AbstractIn Islamic economy, business and ethics should not be viewed as two contradictory things, because, a business which is a symbol of worldly affairs is also considered as an integral part of the things that are investment hereafter. That is, if the orientation of business and investment efforts Hereafter (intended as totality of worship and obedience to God), then the business itself must be in line with the moral rules that based on belief in the afterlife. Even in Islam, understanding the business itself is not limited to world affairs, but also covers all our activities worldwide,